Collapse and convergence: the economic impact of EU membership and institutional improvements in post-Soviet countries - Scott Auriat (The European Journal of Comparative Economics, 2025)
This paper analyzes the economic growth trajectories of post-communist countries that emerged following the collapse of the USSR. I treat the Soviet Union’s sudden dissolution as a natural experiment that triggered rapid institutional changes, providing a unique opportunity to iso- late institutions as the primary driver of growth. The central hypothesis is that countries that swiftly pursued EU membership experienced stronger economic performance than those that did not, with the underlying mechanism being improvements in institutional quality. The findings support this hypothesis, underscoring the pivotal role of high-quality institutional adoption in driving economic growth.